Micro-magnetic response of friction stir welded steel plate at various magnetising frequency and magnetic field intensity - Raja A.R.; Vashista M.; Khan Yusufzai M.Z. (My University, 2025)
The research goal of present experimental work was to analyse the variation in magnetic response (at different magnetising frequency and magnetic field intensity) of IS-2062 steel of grade B upon friction stir welding (FSW). Tungsten carbide tool having 15 mm shoulder diameter was used to weld the steel plates having 3 mm thickness with welding speed of 150 mm per minute and revolving speed of 800 revolutions per minute. Welded steel plates were characterised using Barkhausen Noise analyser. Magnetic response of material, before welding and after welding was recorded in terms of Barkhausen Noise signal parameters that are root mean square (rms) value of signal and number of pulses. Both the signal parameters was observed to correlate well with grain refinement and changes in micro-hardness upon FSW of steel at different analysis parameters such as magnetic field intensity and excitation frequency. Copyright © 2018 Inderscience Enterprises Ltd.